Mexican Americans’ Diabetes Symptom Prevalence, Burden, and Clusters - García, Alexandra A. (Appl Nurs Res, 2019)
AIMS: Type 2 diabetes mellitus (T2DM), serious and increasingly prevalent among Mexican Americans, produces symptoms related to high and low glucose levels, medication side effects, and long-term complications. This secondary analysis explored symptom prevalence, differences among symptom burden levels, and how symptoms clustered. METHODS: Clinical measurements and survey data (demographic, quality of life, and the symptom subscale of the Diabetes Symptom Self-Management Inventory) collected from Mexican American adults with T2DM (n=71) were analyzed for symptom prevalence, differences across levels of symptom burden, and symptom clusters. Agglomerative hierarchical and k-means clustering analyses were performed on a Gower matrix. Internal validation methods and rank aggregation were used to identify the best clustering method of the two techniques and to identify symptoms that clustered together. RESULTS: Participants reported mean=14 symptoms; tiredness and trouble sleeping were most prevalent. People with high symptom burden had significantly lower quality of life and perceptions of worse diabetes severity. Hierarchical clustering produced three symptom clusters: cluster 1=9 symptoms (e.g. intense thirstiness, dry mouth); cluster 2=9 symptoms (e.g., itching skin, weight gain, noise or light sensitivity); cluster 3=13 symptoms (e.g., nervous, headache, trouble concentrating, and memory loss). CONCLUSION: Mexican Americans with T2DM report several co-occurring symptoms. Quality of life is significantly worse for people with high symptom burden. Three distinct symptom clusters were identified. Studies with larger samples are needed to further diabetes symptom science. Clinicians should assess and address patients’ co-occurring symptoms as a potential means of decreasing symptom burden and improving quality of life.